Socio-Culture-Based Classroom Activities in Asia: Do They Work Effectively? - ., Jumariati (KnE Social Sciences, 2017)
Many studies on Second Language Acquisition are carried out based on the sociocultural theory (SCT) to explore learners’ potentials in learning a language. SCT which claims that learning language occurs when learners have the experience to use the language in interaction has been widely used as the basis of the teaching and learning in schools and higher education in Asia. More student-centered and collaborative activities with pair and group works are applied to increase students’ participation and promote language learning within students’ Zone of Proximal Development (ZPD). Within this framework, learners try to expand their ZPD through the assistance from their peers and teacher as the scaffolding of the learning development. However, studies show that implementing the socio-culture-based classroom activities are not trouble-free regarding challenges faced by both sides of the students and the teachers. Consequently, it is essential to have an understanding of how the activities can best work to achieve meaningful learning which promotes the maximum development of students’ actual and potential levels of learning. This paper presents a review of some research on socio-cultural-based education in the context of Asia and describes the findings, benefits and challenges to see how effective the activities are. Keywords: socio cultural theory, classroom activities, benefits, challenges